SYSTEM QUALITY AND USAGE OF INTERNET BANKING FUNCTIONS: ROLE OF CUSTOMER SATISFACTION - Sachithra, R.K.U.; Sritharan, S. (Department of Marketing Management, University of Kelaniya,Sri Lanka, 2017)
The study aims to find out “How do the system quality and the customer satisfaction of internet banking impact on the usage of internet banking services in Badulla District, Sri Lanka?” Further this study makes an attempt to find out whether customer satisfaction of internet banking mediates the relationship between system quality and usage of internet banking services. Usage of internet banking services consists of five dimensions: Fund Transfer Function, Account Control Function, View Only Function, Credit Product Function, and Apply for New Product Function. System Quality of Internet Banking consists of three dimensions: Accessibility, User Friendly Website and Security. Customer Satisfaction of Internet Banking consists two dimensions: Customer Attitude and Customer Loyalty. In a study of 190 internet banking users selected by convenient sampling, correlation and regression analysis were performed to answer the study objectives. The system quality dimensions have significant positive influence on customer satisfaction, which in turn has a significant positive impact on usage of internet banking services. The mediation role of customer satisfaction on system quality and usage of internet banking relationship is also confirmed. The findings of this study assist the bank managers, academics and practitioners to develop and implement system quality and usage of internet banking related strategies.
Keywords: Internet banking; Internet banking services (IBS); System quality; Customer satisfaction